THE BEST PRESCHOOL RECOMMENDATION APPLICATION USING THE ELECTRE METHOD - Siregar, Iqbal Kamil; Handoko, Wiwin (Lembaga Penelitian dan Pengabdian Kepada Masyarakat (LPPM) STMIK Royal Kisaran, 2024)
Abstract: This research aims to build a recommendation system that can help parents determine the best Pendidikan Anak Usia Dini (PAUD) using the ELECTRE (Elimination and Choice Translating Reality) method. The electre method was chosen because of its ability to handle Multi-Criteria Decision Making (MCDM) problems, which allows evaluating alternatives based on various relevant criteria. This system is designed to identify and assess PAUD based on a number of important criteria, such as facilities, location, teacher-student ratio, curriculum, accreditation and reputation. Each criterion is given a weight according to its level of importance, which is determined based on parental preferences and applicable educational standards. Data is collected from various sources and processed using artificial intelligence techniques to ensure accuracy and relevance. The electre method is then used to evaluate and compare between PAUD. The research results show that the recommendation system developed is able to provide accurate and relevant PAUD recommendations, as well as increasing user satisfaction in the PAUD selection process. This research makes a significant contribution to the field of decision support systems and education, by showing the practical application of the electre method in determining the best PAUD. It is hoped that the results of this research can inspire the development of similar recommendation systems in other educational fields, as well as help in improving the quality of early childhood education through the use of advanced technology.Keywords: artificial intelligence; electre method; multi-criteria decision making (mcdm); paud. Abstrak: Penelitian ini bertujuan untuk membangun sistem rekomendasi yang dapat membantu orang tua dalam menentukan Pendidikan Anak Usia Dini (PAUD) terbaik dengan menggunakan metode ELECTRE (Elimination and Choice Translating Reality). Metode electre dipilih karena kemampuannya dalam menangani masalah Multi-Criteria Decision Making (MCDM), yang memungkinkan evaluasi alternatif berdasarkan berbagai kriteria yang relevan. Sistem ini dirancang untuk mengidentifikasi dan menilai PAUD berdasarkan sejumlah kriteria penting, seperti fasilitas, lokasi, rasio guru-murid, kurikulum, akreditasi dan reputasi. Setiap kriteria diberikan bobot sesuai dengan tingkat kepentingannya yang ditentukan berdasarkan preferensi orang tua dan standar pendidikan yang berlaku. Data dikumpulkan dari berbagai sumber dan diproses menggunakan teknik kecerdasan buatan untuk memastikan akurasi dan relevansi. Metode electre kemudian digunakan untuk melakukan evaluasi dan perbandingan antar PAUD. Hasil penelitian menunjukkan bahwa sistem rekomendasi yang dikembangkan mampu memberikan rekomendasi PAUD yang akurat dan relevan, serta meningkatkan kepuasan pengguna dalam proses pemilihan PAUD. Penelitian ini memberikan kontribusi signifikan pada bidang sistem pendukung keputusan dan pendidikan, dengan menunjukkan aplikasi praktis dari metode electre dalam penentuan PAUD terbaik. Diharapkan, hasil penelitian ini dapat menginspirasi pengembangan sistem rekomendasi serupa di bidang pendidikan lainnya, serta membantu dalam meningkatkan kualitas pendidikan anak usia dini melalui pemanfaatan teknologi canggih.Kata kunci: kecerdasan buatan; metode electre; multi-criteria decision making (mcdm); paud.